Sulfur poisoning of co-precipitated Ni–Al catalysts for the methanation of CO2. (July 2019) - Wolf, Moritz; Schüler, Christian; Hinrichsen, Olaf
Highlights: Sulfur poisoning of a wide range of co-precipitated Ni–Al catalysts by H2 S and SO2 . Thermographic measurements of a moving reaction front through a fixed-bed microreactor. Validation of a site-blocking mechanism. Prediction of catalyst lifetimes via H2 adsorption capacity. Kinetic description of intrinsic methanation activity as a function of sulfur coverage. Abstract: This study provides deep insights into the mechanism and kinetics of sulfur poisoning of co-precipitated Ni catalysts for the methanation of CO2 . A large number of catalysts with different Ni loadings were poisoned with 5 ppm of H2 S and SO2 at equilibrium conditions (H2 /CO2 /Ar=4/1/5, 400 °C, 1 bar). Prior to the complete loss of activity, thermography reveals a moving reaction front through the fixed-bed microreactor. The stability of catalysts depends on available Ni surface atoms. H2 chemisorption and post-mortem CHNS analysis show an average S/Ni * surface atom ratio of 0.73 ± 0.02. Based on this stoichiometry, a model for predicting catalyst lifetimes is derived and extrapolated to different H2 S partial pressures. In an ex situ poisoning approach, liquid (NH4 )2 S was used to adjust sulfur coverages between 0 and 0.73. Activity measurements under differential conditions reveal an activity loss of more than 80% at coverages as low as θ S = 0.2. A kinetic description based on a Maxted-type correlation is derived. The strong dependence of activity on sulfur coverage is explained by the space requirements of CO2 adsorption on Ni 0 . Activation energies of non-poisoned and poisoned samples are similar and in the range of 80–87 kJ/mol. Sulfur poisoning is therefore ascribed to site blockage rather than electronic effects.